2020
DOI: 10.1111/epi.16669
|View full text |Cite
|
Sign up to set email alerts
|

KA‐104, a new multitargeted anticonvulsant with potent antinociceptive activity in preclinical models

Abstract: Objective: The main objective of the present work was to assess the utility of KA-104 as potential therapy for drug-resistant seizures and neuropathic pain, and to characterize its druglike properties in a series of absorption, distribution, metabolism, excretion and toxicity (ADME-Tox) studies. We also aimed to establish its mechanism of action in electrophysiological studies. Methods: The activity of KA-104 against drug-resistant seizures was tested in the mouse 6-Hz (44-mA) model, whereas the antinociceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…In general, pyrrolidine-2,5-dione derivatives displayed satisfied stability as their conversion into metabolites was lower than 30% during 120 min incubation with HLMs. These results correlate with our previous studies, where high metabolic stability within this chemical group was also found [9,12,14,15,37]. Compound 4 showed the highest susceptibility for enzymatic biotransformations (71.4% of parent compound remained in the reaction mixture; see Figure S1, Supplementary Materials), resulting in double-hydroxylations (M1), pyrrolidine-2,5-dione ring hydrolysis (M2), or monohydroxylation (M3) as the most probable metabolic pathways (Figures S2 and S7, Supplementary Materials).…”
Section: Metabolic Stabilitysupporting
confidence: 93%
“…In general, pyrrolidine-2,5-dione derivatives displayed satisfied stability as their conversion into metabolites was lower than 30% during 120 min incubation with HLMs. These results correlate with our previous studies, where high metabolic stability within this chemical group was also found [9,12,14,15,37]. Compound 4 showed the highest susceptibility for enzymatic biotransformations (71.4% of parent compound remained in the reaction mixture; see Figure S1, Supplementary Materials), resulting in double-hydroxylations (M1), pyrrolidine-2,5-dione ring hydrolysis (M2), or monohydroxylation (M3) as the most probable metabolic pathways (Figures S2 and S7, Supplementary Materials).…”
Section: Metabolic Stabilitysupporting
confidence: 93%
“…The higher acute neurotoxicity (motor impairment) in the rotarod test may result from very a fast penetration to the murine brain and a much higher concentration of salts in the CNS compared to the parent and hardly water-soluble compounds as it was observed for compound 14 and its direct analogue I (see compound KA-104, ref. [ 7 ]), in the pharmacokinetic studies (pharmacokinetic data for compound 14 are shown below).…”
Section: Resultsmentioning
confidence: 99%
“…Our most recent studies led to the identification of several hybrid compounds belonging to a group of pyrrolidine-2,5-dione derivatives, which proved to be promising candidates for further preclinical development in epilepsy and neuropathic pain indications [ 6 , 7 , 8 ]. It should be mentioned here that succinimide derivatives have been explored by many research groups in the CNS area, i.e., for the identification of new anticonvulsant and antidepressant agents [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations